1998
DOI: 10.1002/(sici)1097-4644(19980601)69:3<291::aid-jcb7>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

TGF-β1 modifications in nuclear matrix proteins of osteoblasts during differentiation

Abstract: Nuclear matrix protein (NMP) composition of osteoblasts shows distinct two-dimensional gel electrophoretic profiles of labeled proteins as a function of stages of cellular differentiation. Because NMPs are involved in the control of gene expression, we examined modifications in the representation of NMPs induced by TGF-beta1 treatment of osteoblasts to gain insight into the effects of TGF-beta on development of the osteoblast phenotype. Exposure of proliferating fetal rat calvarial derived primary cells in cul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2000
2000
2004
2004

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…It also is reported that direct coculture of osteoblasts and osteoclast precursors induces maturation of osteoclast‐like cells but decreases the ALP activity expressed by osteoblasts (7) . Transforming growth factor β (TGF‐β) increases osteoblast recruitment, differentiation, production of matrix proteins, and modification of mineralization, leading to enhanced trabecular bone formation (40,41) . Interestingly, Jilka et al (42) recently showed that TGF‐β prevents osteoblast apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…It also is reported that direct coculture of osteoblasts and osteoclast precursors induces maturation of osteoclast‐like cells but decreases the ALP activity expressed by osteoblasts (7) . Transforming growth factor β (TGF‐β) increases osteoblast recruitment, differentiation, production of matrix proteins, and modification of mineralization, leading to enhanced trabecular bone formation (40,41) . Interestingly, Jilka et al (42) recently showed that TGF‐β prevents osteoblast apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous reports showed that the growth factors PDGF‐BB [Kim et al, 1999] and FGF‐2 [Bae et al, 2000] stimulate OP expression in the early stages of MC3T3‐E1 cell differentiation but suppress it strongly in the later mineralization stage. Nuclear matrix components and their organization change dramatically with cell differentiation, and the changes would greatly influence the use of the transcriptional machinery [Lindenmuth et al, 1998]. Thus, OP regulation by growth factors relies on the cellular environment.…”
Section: Discussionmentioning
confidence: 99%